Ovine Mesenchymal Stromal Cells: Morphologic, Phenotypic and Functional Characterization for Osteochondral Tissue Engineering - Sanjurjo-Rodríguez, Clara (PLoS One, 2017)
INTRODUCTION: Knowledge of ovine mesenchymal stromal cells (oMSCs) is currently expanding. Tissue engineering combining scaffolding with oMSCs provides promising therapies for the treatment of osteochondral diseases. PURPOSE: The aim was to isolate and characterize oMSCs from bone marrow aspirates (oBMSCs) and to assess their usefulness for osteochondral repair using β-tricalcium phosphate (bTCP) and type I collagen (Col I) scaffolds. METHODS: Cells isolated from ovine bone marrow were characterized morphologically, phenotypically, and functionally. oBMSCs were cultured with osteogenic medium on bTCP and Col I scaffolds. The resulting constructs were evaluated by histology, immunohistochemistry and electron microscopy studies. Furthermore, oBMSCs were cultured on Col I scaffolds to develop an in vitro cartilage repair model that was assessed using a modified International Cartilage Research Society (ICRS) II scale. RESULTS: oBMSCs presented morphology, surface marker pattern and multipotent capacities similar to those of human BMSCs. oBMSCs seeded on Col I gave rise to osteogenic neotissue. Assessment by the modified ICRS II scale revealed that fibrocartilage/hyaline cartilage was obtained in the in vitro repair model. CONCLUSIONS: The isolated ovine cells were demonstrated to be oBMSCs. oBMSCs cultured on Col I sponges successfully synthesized osteochondral tissue. The data suggest that oBMSCs have potential for use in preclinical models prior to human clinical studies.